Exploring Family Strength: Vulnerability Factors and the Role of Spirituality in Family Resilience During COVID-19 Pandemic - Islamia, Intan; Marliani, Rosleny (ANFUSINA: Journal of Psychology, 2023)
This research explores the relationship between family vulnerability, spirituality, and resilience during the Covid-19 pandemic. With a quantitative approach and cross-sectional study design, samples were taken randomly using a random sampling method, involving 189 husbands/wives willing to participate. Data collection was carried out through interviews (both online and offline) using a modified questionnaire based on the Sunarti (2021) scale to measure family resilience and family vulnerability, as well as Underwood's (2003) DSES (Daily Spiritual Experience Scale) scale to measure spirituality. The research results show that there is a significant negative relationship between family vulnerability and family resilience, while spirituality has a significant positive correlation with family resilience. In addition, family vulnerability and spirituality together contributed 17.2% to the variation in family resilience. These findings contribute to understanding family resilience in the COVID-19 era and indicate the need for further discussion in future research.Keywords: Family resiliency, family vulnerability, spirituality, COVID-19